Interconnection between injectable omeprazole and clopidogrel tablet: a comprehensive analysis of clinical and pharmacological implications - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
Therapeutic synergy is a sought-after goal in contemporary medical practice, aiming to maximize therapeutic benefits while minimizing pharmacological adverse effects (Chowdhury et al., 2020). However, the drug interaction between injectable omeprazole and clopidogrel tablet emerges as a crucial clinical and pharmacological concern. Clopidogrel, a widely used antiplatelet agent in cardiovascular event prevention, and omeprazole, a proton pump inhibitor often prescribed for gastrointestinal disorders, are frequently co-administered in patients with elevated cardiovascular risk (Bhurke et al., 2018). Nevertheless, recent studies suggest that this combination might compromise the antiplatelet efficacy of clopidogrel due to potential pharmacokinetic and pharmacodynamic interactions.